High Speed Rail and Access Transit Networks - Brunello, Lara Rita (Springer International Publishing, 2018)
This book examines the promise of High Speed Rail (HSR) technologies to win market share from carbon-intensive air transport through the strategic optimization of rail productivity and efficiency. While the positive impacts of HSR at both urban and long-distance levels are well-documented, this resource focuses on what has been a challenging area for HSR deployment historically: the integration of HSR accessibility at the regional level. The author provides tools and methods to better measure the feasibility of integrating regional HSRwith existing transport networks, and includes in-depth case studies to demonstrate the contributions of expanded high speed rail access on sustainable development. Shares options for maximizing efficiency and effectiveness of high speed rail transport; Compares strategies for integrating urban, long-distance, and regional high speed rail transport; Explores new dimensions of high speed rail deployment by l inking transit networks with increased regional accessibility.